Norbixin binding to whey protein isolate - alginate electrostatic complexes increases its solubility and stability. (April 2020) - Møller, Anders Hauer; Wijaya, Wahyu; Jahangiri, Amita; Madsen, Bjoern; Joernsgaard, Bjarne; Vaerbak, Signe; Hammershøj, Marianne; Van der Meeren, Paul; Dalsgaard, Trine Kastrup
Abstract: Norbixin is a carotenoid extracted from the Annatto plant ( Bixa orellana ) and widely used as a natural colorant in pharmaceuticals, cosmetics and food. It is water-soluble at neutral and alkaline pH, but below neutral pH, norbixin starts to precipitate limiting the use in acidic food products. As a new approach to enhance the solubility and stability of norbixin in aqueous solution under acidic conditions, the colorant was applied in the presence of whey protein isolate (WPI) and alginate (ALG). Addition of WPI prevented norbixin precipitation between pH 2 and pH 7 except at the pI of WPI, pH 5. The visual appearance, colorimetric measurements and a blue shift in the absorbance spectrum indicated that norbixin formed H -aggregates at pH < 7, but the aggregates were stabilized by WPI addition. Fluorescence spectroscopy measurements indicated interactions between both soluble norbixin and WPI at pH 7 and aggregated norbixin and WPI at pH 3. Particle size measurements indicated formation of complexes between norbixin aggregates and WPI. Additionally to preventing the precipitation of norbixin, the WPI-norbixin interaction also increased the color stability of norbixin during storage at both neutral and acidic pH. At pH 5, isoelectric precipitation of WPI was prevented by the inclusion of ALG, likely due to electrostatic interactions between WPI and ALG leading to the formation of norbixin, WPI and ALG complexes. The use of WPI and ALG complexation of norbixin can therefore be a new way to expand the usage of norbixin coloring of foods at acidic pH conditions. Graphical abstract: Image 1 Highlights: Norbixin and whey protein interact at neutral and acidic pH. Below neutral pH norbixin aggregates and whey protein form complexes. Except for pH = pI, whey protein-norbixin complexation prevents norbixin precipitation. Alginate prevents isoelectric precipitation of the whey protein–norbixin complexes. Interactions between norbixin and WPI increase norbixin color stability.